Estudo teórico de vasos de pressão de paredes grossas e paredes compostas - Silva, Karina Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Pressure vessel is highly used in the industry for the storage of the most diverse types of fluids under various operating conditions. However, despite of the versatility of this equipment, the design of a pressure vessel requires serious care and compliance with a several norms and standards to ensure its safety and suitable performance. The industrial and technological need requires the construction of increasingly resistant and economical pressure vessels, which are suitable for services under extreme operating conditions, such as for use in nuclear reactors. This work promotes a case study around two types of pressure vessels used for services in extreme conditions: thick-walled vessels and multilayer vessels. The case study deals with the calculation of the minimum allowable thicknesses for the cylinders of both equipment according to the premises and equations suggested by the ASME Code, Section VIII, Divisions I and II, besides promoting the calculation of the maximum tensions acting in each vessel through equations obtained from the literature. Finally, at the end of the paper, the results obtained through the formulas of the Code and ones obtained from the equations of the literature are compared and it is possible to verify that the values obtained are consistent with those found in other works of the same type, in addition to meeting the requirements of the standard referenced

Vasos de pressão são equipamentos amplamente utilizados na indústria para o armazenamento dos mais diversos tipos de fluidos sob variadas condições de operação. Porém, apesar da versatilidade deste equipamento, o projeto de um vaso de pressão exige cuidados específicos e o cumprimento de uma série de normas e padrões para a garantia de sua segurança e bom desempenho. A necessidade industrial e tecnológica exige a construção de vasos de pressão mais resistentes e econômicos, sendo adequados para serviços em condições de operação extremas, como por exemplo o emprego em reatores nucleares. Este trabalho promove um estudo de caso em torno de dois tipos de vasos de pressão utilizados para serviços em condições extremas: vasos de paredes grossas e vasos de paredes compostas. O estudo de caso aborda o cálculo das espessuras mínimas admissíveis para os cilindros de ambos os equipamentos de acordo com as premissas e equações sugeridas pelo Código ASME, Seção VIII, Divisões I e II, além de promover o cálculo das tensões máximas atuantes em cada vaso através de equações obtidas da literatura. Por fim, compara-se os resultados obtidos através das fórmulas do Código e das equações da literatura e verifica-se que os valores obtidos estão coerentes com o encontrado em outros trabalhos de mesmo caráter, além de atenderem aos requisitos da norma referenciada
Theoretical study of thick-walled pressure vessels and composite walls
Keywords: Vasos de pressão; Fluidos; Reatores nucleares; Pressure vessels